Pemberdayaan guru melalui kegiatan pelatihan media pembelajaran di SMA Negeri 7 Takalar - Mustari S. Lamada; Sugeng A. Karim (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
The objectives of this study were to introduce Macromedia Flash software to teachers of SMA Negeri 7 Takalar and to train teachers of SMA Negeri 7 Takalar to create learning media. The output of this study is the learning media used in the learning process and the improvement of the quality of learning by clarifying the presentation of messages so that they are not verbalistic, eliminating passivity on the subject of learning, and raising motivation in the subject of learning.The results of this research are learning media created by teachers of SMA 7 Takalar by looking at their high enthusiasm and motivation to apply the learning media. In addition, adequate school facilities and infrastructure and some young teachers who already have initial media skills presentation media, especially Microsoft PowerPoint.